2013
DOI: 10.1007/s10433-013-0302-8
|View full text |Cite
|
Sign up to set email alerts
|

The balance of intergenerational family transfers: a life-cycle perspective

Abstract: The aim of this study is to determine the likelihood and net amount of parent-child transfers over the adult life cycle across European welfare regimes. The study introduces an economic life-cycle model of family transfers to describe the evolution of family exchanges across generations over time, which reveals a nonlinear relationship of age and net family transfers. Furthermore, it refines the method of estimating parent-child net transfers. Data come from the Survey of Health, Ageing, and Retirement in Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Inside families, the interests of younger generations are regularly championed by older ones. Research consistently shows an impressive flow of resources from older parents to their adult children until very old age (Mudrazija, 2013), leading some to refer to the safety nets and scaffolding provided by parents to their adult progeny (Swartz, Kim, Uno, Mortimer, & O'Brien, 2011; see also Connidis, 2010). Middle-age and older parents often help with housing.…”
Section: Intergenerational Ties: Inside Familiesmentioning
confidence: 99%
“…Inside families, the interests of younger generations are regularly championed by older ones. Research consistently shows an impressive flow of resources from older parents to their adult children until very old age (Mudrazija, 2013), leading some to refer to the safety nets and scaffolding provided by parents to their adult progeny (Swartz, Kim, Uno, Mortimer, & O'Brien, 2011; see also Connidis, 2010). Middle-age and older parents often help with housing.…”
Section: Intergenerational Ties: Inside Familiesmentioning
confidence: 99%
“…Scholars have devoted considerable attention to comparative studies on the exchange of financial transfers, help and care, as well as emotional closeness and proximity between adult family generations across European countries ( e.g. Attias-Donfut, Ogg and Wolff 2005; Deindl and Brandt 2011; Hank 2007; Igel and Szydlik 2011; Mudrazija 2014). These studies document that most help within the family – in kind or emotionally – is transferred between parents and their children, to the extent that what Bengtson (2001) labels as the ‘decline of the family’ still seems to be a myth.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that financial transfers from the old to the young are more common in those living as a couple, those with higher socio-economic status and education and those with good health. Mudrazija (2014) also showed that net transfers of money from parents to children only modestly decrease with age. Additionally, Fritzell and Lennartsson (2005) have found that within this clear downward flow of financial transfers, there is a class and income gradient as both giving and receiving are more common among people in the higher social strata.…”
Section: Literature Review: Family Transfers and Their Determinantsmentioning
confidence: 99%
“…Since our article does not have a comparative perspective, we will not focus on these macro-level determinants; however, one needs to point out that financial transfers are less common in countries with strong welfare states and developed social policies, which also enable more downward financial flows (from parents to children) (e.g., Björnberg & Ekbrand, 2008;Deindel & Brandt, 2011;Brandt & Deindl, 2013;Mudrazija, 2016). Additionally, the decrease in downward transfers that is a characteristic of the increasing age of parents is slower in sociodemocratic countries than in Mediterranean countries (Mudrazija, 2014). Deindel and Brandt (2011) showed that financial transfers to parents were very rare in Europe as in only 2% of the dyads was money transferred upwards, while financial transfers from parents to children were more frequent, occurring in around 4% of the dyads.…”
Section: Literature Review: Family Transfers and Their Determinantsmentioning
confidence: 99%